Database Systems: Design, Implementation, and Management, Eighth Edition - Rob, Peter (Course Technology, 2011)
Database Systems: Design, Implementation, and Management, Eighth Edition, a market-leader for database texts, gives readers a solid foundation in practical database design and implementation. The book provides in-depth coverage of database design, demonstrating that the key to successful database implementation is in proper design of databases to fit within a larger strategic view of the data environment. Updates for the eighth edition include additional Unified Modeling Language coverage, expanded coverage of SQL Server functions, all-new business intelligence coverage, and added coverage of data security. With a strong hands-on component that includes real-world examples and exercises, this book will help students develop database design skills that have valuable and meaningful application in the real world.